PENGEMBANGAN BEKA’ ECOTOURISM GUNA MENDUKUNG KONSERVASI KAKAKTUA KECIL JAMBUL KUNING DAN EKONOMI MASYARAKAT PULAU MASAKAMBING - Ihsannudin, Ihsannudin; Sriyono, Sriyono; Safi', Safi'; Kuntadi, Ebban Bagus (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2024)
Masakambing island, having only one village Masakambing and located in Sumenep Regency, East Java, has area 7,79 square kilometers. This island is designated as Essential Ecosystem Area (KEE) through East Java Governor’s decree No. 188/166/2020 because it has High Conservation Valued Area (ABKT) as the habitat of endemic yellow-crested cockatoos (Caccatua sulphurea abbotti). The wildlife having local name Beka’ is critically endangered because there are only 22 birds left in the wild. Furthermore, the society in Masakambing is motivated and eager to save yellow-crested cockatoos when they have economic benefits, one of them is ecotourism. The implementation of ecotourism should refer to the preservation, the involvement of local people, and interpretation–education content while considering safety and hospitality. Accordingly, this emerges an idea of Beka’ Ecotourism development as ecotourism activity-based conservation of yellow-crested cockatoos. The development is conducted for the institutional capacity of Pokdarwis Beka’ Island in terms of institution, legality, and governance. Besides, safety assurance, interpretation-education, and hospitality such as homestay and food-beverage service and as well as promotion through social media and network connectivity are also developed